2018
DOI: 10.1016/j.ceramint.2018.07.119
|View full text |Cite
|
Sign up to set email alerts
|

Bulk Li mobility enhancement in Spark Plasma Sintered Li(7−3x)AlxLa3Zr2O12 garnet

Abstract: Li (7−3x) Al x La 3 Zr 2 O 12 (LLAZO) Al-doped garnets display high ionic conductivity in the range of ~10 -4 S.cm -1 at room temperature and are thus envisioned for future solid-state batteries. In this study, LLAZO powders with two doping levels were synthetized using a solid-state route and sintered using Spark Plasma Sintering (SPS). Both pristine and SPS crushed pellet powders were investigated using X-Ray Diffraction (XRD) confirming the formation of the most conducting cubic phase. Ionic conductivity me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 29 publications
0
5
0
Order By: Relevance
“…10,[51][52][53][54][55][56] In this work, we concentrated on designing a tri-functioal modification strategy, by employing Li6.4La3Al0.2Zr2O12 (LLAZO) precursor (Li, Al, La, Zr based salts) to coat LNMO precursor powders followed by calcination at 820 o C to form the coating layer and LNMO material simultaneously. [57][58] In this case, LLAZO coating layer restricts the growth of LNMO precursor particles during crystalization process. 59 Moreover, it is expected that alien ions will diffuse into the lattice of LNMO.…”
Section: Introductionmentioning
confidence: 99%
“…10,[51][52][53][54][55][56] In this work, we concentrated on designing a tri-functioal modification strategy, by employing Li6.4La3Al0.2Zr2O12 (LLAZO) precursor (Li, Al, La, Zr based salts) to coat LNMO precursor powders followed by calcination at 820 o C to form the coating layer and LNMO material simultaneously. [57][58] In this case, LLAZO coating layer restricts the growth of LNMO precursor particles during crystalization process. 59 Moreover, it is expected that alien ions will diffuse into the lattice of LNMO.…”
Section: Introductionmentioning
confidence: 99%
“…Lithium-ion conductivity values of Al-doped solid electrolytes are equal to ~10 −4 S/cm at 25 °C [ 20 , 28 ]. Li 7−3x Al x La 3 Zr 2 O 12 solid electrolytes were obtained by various methods (solid-state reaction, sol–gel, spark plasma sintering, self-consolidation method) and under different final heat-treatment conditions, which have a significant effect on the lithium content in the compound, the stabilization of highly conductive cubic modification, the phase composition and density of ceramic membranes, and, as a result, on the total conductivity of the obtained solid electrolytes [ 20 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 ]. Rangasamy et al [ 36 ] studied the effect of the Li and Al ions concentration on the cubic LLZ formation.…”
Section: Resultsmentioning
confidence: 99%
“…Castillo et al studied Li and Al distribution behaviors and Li mobility in Al-doped LLZO after SPS treatment. [232] The results indicated that SPS treatment caused a redistribution of Al ions into Li sublattice, which resulted in enhancement of Li mobility and consequently higher bulk conductivity. [233] Despite the abovementioned advantages, impurity phase, such as La 2 Zr 2 O 7 , is easily produced if the powder preparation process is not well controlled.…”
Section: Advanced Sintering Techniques and Other Methodsmentioning
confidence: 94%
“…studied Li and Al distribution behaviors and Li mobility in Al‐doped LLZO after SPS treatment. [ 232 ] The results indicated that SPS treatment caused a redistribution of Al ions into Li sublattice, which resulted in enhancement of Li mobility and consequently higher bulk conductivity. [ 233 ]…”
Section: Processing Llzo Ceramicsmentioning
confidence: 99%